(untitled) (Encuentros, 2016)
The present research was implemented for to obtain a demographic characterization of a population of informal caretaker of ancients with ictus and dementia, and to identify the statistical relationship among demographics characteristics and disease associated with the caretaker job. Was executed a descriptive study with the participation of 237 caretaker. Was applied a Questionnaire for to obtain the necessary information. The data analysis involved descriptive and correlational statistical test. The 71% of caretakers was woman and 28.3% man. The middle age was 49.83 years old, and the middle time of caretaker´s dedication was 42.86 month. The 49.4% of caretakers are son, wife or husband of the patient, thus the 50.6% have other link. The 53.2% is caretaker all the time, and the 46.7% only in part time. Keywords: Caretakers, Informal caretakers, Dementia, Ictus, Demographic characterization